A National Survey of Spinal Cord Stimulation Trial‐to‐Permanent Conversion Rates. Issue 2 (13th June 2014) - Huang, Kevin T.; Martin, Joel; Marky, Andrew; Chagoya, Gustavo; Hatef, Jeff; Hazzard, Matthew A.; Thomas, Steven M.; Lokhnygina, Yuliya; Lad, Shivanand P.
<x xml:space="preserve">Abstract</x> Objectives Conversion rates from trial leads to permanent spinal cord stimulation (SCS) systems have recently come under scrutiny. Our goal was to examine the rate of conversion from trial lead to permanent system placement as well as identify factors associated with successful SCS conversion. Materials and Methods We designed a large retrospective analysis using the Thomson Reuters MarketScan database. We included all patients who underwent a percutaneous trial of neurostimulatory electrodes from the years 2000 to 2009 who were aged 18 and older. Patients were then tracked to see if they went on to receive a permanent SCS system. Patients were also analyzed in univariate and multivariate models to identify factors associated with successful conversion. Results A total of 21, 672 unique instances of percutaneous trials were identified. Overall, 41.4% of those receiving trials went on to have a permanent SCS system installed within the subsequent three months. Factors associated with increased likelihood of successful conversion included having commercial insurance (43% vs. 37%, p < 0.0001), younger age (43% for those aged 35–44 vs. 39% for those aged 65 and older, p < 0.0001), and never having had a previous percutaneous trial attempt (44% for first‐time trials vs. 27% for those on their second trial vs. 14% for those on their third or later trial, p < 0.0001). In multivariate analysis, we found significant variation in conversion rate by geographic area (patients in the North Central region vs. Northeast region: odds ratio 1.48, 95% confidence interval [1.31, 1.66]; p < 0.0001). Conclusions In this study of a national cohort of patients, we identified specific factors associated with higher conversion rates, along with significant geographical variation. In general, there is a need for better patient selection by physicians who practice neuromodulation.